Product Purchase Decisions On Shopee The Study Examines The Impact Of Product Quality, Price, And Promotion On Product Purchase Decisions On Shopee - Vicky Frandian Tambun; Jamaluddin Jamaluddin; Tigor Ananda PARADONGAN Saragi Napitu; Hendra Saputra (Cita konsultindo, 2024)
E-commerce has become a vital part of global trade activities, as platforms like Shopee offer a variety of products to consumers through various marketing strategies. This study aims to investigate the impact of product quality, price, and promotion on purchasing decisions of products on Shopee. The research method employs a quantitative approach using an online survey targeting active Shopee users in Indonesia. The sample is intentionally selected and consists of respondents who possess prior expertise in making purchases on Shopee. Data dikumpulkan melalui survei online yang mengukur pandangan konsumen terhadap mutu produk, harga, promosi, dan kebiasaan pembelian. Data analysis involves the use of regression techniques to test research hypotheses. The research findings indicate that the quality of products, price, and promotion significantly influence consumer purchasing decisions on Shopee. The primary objective of the study is to provide Shopee sellers with comprehensive insights into the key aspects they should consider when formulating a successful pricing plan for their products on the e-commerce platform.